Streaming Metadata Objek Tiga Dimensi (3D) - Yuliar Syamyu Dhuhaa; Anang Kukuh Adisusilo; Noven Indra Prasetya (Melek IT : Information Technology Journal, 2016)
The more rapid development of multimedia , one of them is three-dimensional object .Threedimensional object to have a high because the complexity of many elements .When want to see a model of threedimensional object have to wait longer .Needed a technology that canreduce waiting time to see an object three dimensions of the one with a stream . Streaming is the process of sending data from the media source toward client in real-time .Metadata having the size of a file that smaller than the original data .By using this is then done using streaming metadata to accelerate in accessing model three-dimensional object .The result of this research to display threedimensional object of wake up space cube and the beam in a stream by taking dataalternately start of an object and to the color in a cube and a bea visible 5.6 of pictures ,pictures andimages 5.7 5.8 , 5.9 picture .